Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00345-007-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

The bone-anchor sub-urethral sling for the treatment of iatrogenic male incontinence: subjective and objective assessment after 41 months of mean follow-up

Abstract: BAUS implantation is a safe, effective, minimally invasive option for iatrogenic male incontinence due to ISD. It compares favourably with AUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 27 publications
2
31
0
6
Order By: Relevance
“…Previous studies have not found any significant obstructive impact on the micturion pattern of patients when using this technique [11, 13, 19-21, 26, 27]. Giberti et al [20] reported that, of the urodynamic parameters recorded, only increased VLPP was successful in postoperative outcome. Hairston and Ghoniem [28] utilized fluorourodynamic studies and demonstrated an increase in VLPP in patients undergoing the male sling procedure, but without an appreciable change in urethral or voiding pressures.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have not found any significant obstructive impact on the micturion pattern of patients when using this technique [11, 13, 19-21, 26, 27]. Giberti et al [20] reported that, of the urodynamic parameters recorded, only increased VLPP was successful in postoperative outcome. Hairston and Ghoniem [28] utilized fluorourodynamic studies and demonstrated an increase in VLPP in patients undergoing the male sling procedure, but without an appreciable change in urethral or voiding pressures.…”
Section: Discussionmentioning
confidence: 94%
“…Insbesondere unter Berücksichtigung der präoperativen Inkontinenzrate wurden dann lediglich Erfolgsraten von 67/50/0% bei leichter/mittelgradiger/schwerer Inkontinenz erzielt [6]. Als Komplikationen dieser Methode werden typischerweise perinealer Schmerz und Taubheitsgefühl von bis zu 75% der Patienten angegeben [15,35,38].…”
Section: Invance-bandunclassified
“…Biological grafts have also been employed; however, they do not appear to provide comparable efficacy to woven polypropylene mesh. 19 Composite grafts have also been used successfully. 30,31 American Medical Systems launched an AdVance transobturator sling in 2006, proposed to impart benefit not only via suburethral compression, but also by relocating and elevating the bulbar urethra more proximally.…”
Section: Kevin V Carlson Md Frcscmentioning
confidence: 99%
“…The development of titanium bone screws to anchor the mesh into the pubic rami subsequently allowed the mesh to be placed through an entirely transperineal approach in a minimally invasive fashion, while allowing solid long-lasting fixation. Short-and medium-term follow-up from a number of single-centre studies are now available [15][16][17][18][19] and are comprehensively reviewed by Comiter 20 and by Sousa-Escandon and colleauges. 21 Cure rates range from 37% to 87%, cure or improved rates from 64% to 100% and satisfaction rates are typically 70% to 80%.…”
Section: Kevin V Carlson Md Frcscmentioning
confidence: 99%